Is hippocampal volume an accurate and reliable early marker of Alzheimer's disease?: Neuroimaging / differential diagnosis. (7th December 2020) - Gentreau, Mélissa; Maller, Jerome J; Meslin, Chantal; Cyprien, Fabienne; Ritchie, Karen; Artero, Sylvaine
Abstract: Background: It is challenging to predict when and which individuals will progress to Alzheimer's disease (AD) to facilitate enrollment in clinical trials. Hippocampal volume (HV) considered as a fundamental structure for cognition is one of the key emerging imaging markers to improve Alzheimer's disease risk prediction. There are numerous examples of HV reduction among patients with AD and those at risk for AD. However most evidence is derived from research cohorts or clinical populations with short follow‐up, and the extent to which hippocampal degeneration predict long‐term AD remains somewhat unclear. Moreover, hippocampus being damaged by a variety of stimuli including nutrition, sleep, inactivity, stress and depressive symptoms, it may also play a role on mild cognitive decline in the context of normal aging. To address this issue we studied the long term association between HV and the risk of 1) incident dementia and 2) mild cognitive decline in normal aging. Method: We studied 510 dementia‐free persons from the ESPRIT cohort, aged over 65 years. All participants underwent magnetic resonance imaging (1.5 T) at baseline. We used both manual and automated methods (Freesurfer 6.0) to measure HV. A cognitive test battery (global cognition, visual memory, executive function, verbal fluency) was performed, and participants were followed by neurologists for incident dementia at 2, 4, 7, 10, 12 and 15 years. We tested the association between HV and the risk of dementia and mild cognitive decline using respectively Cox proportional hazards and linear mixed models. Result: 42 participants developed AD. After adjustment by potential confounder (age, sex, education, ApoE4, depression, antidepressive drugs, alcohol, sleep, baseline MMSE score, intracranial volume) right and left HV were significantly associated with dementia (p<0.01) but also with mild cognitive decline in normal aging (p<0.02). Conclusion: In a community‐dwelling population, we report evidence that HV predict both long term incident dementia and mild cognitive decline in normal ageing casting doubt on the utility of this structure as an early biomarker of AD using only a single measure. However, this measure could be used in general population framework to target subject at risk of cognitive decline and to develop preventive strategies.